2021
DOI: 10.1038/s41394-020-00380-4
|View full text |Cite
|
Sign up to set email alerts
|

Brain–computer interface-triggered functional electrical stimulation therapy for rehabilitation of reaching and grasping after spinal cord injury: a feasibility study

Abstract: Study design Feasibility and preliminary clinical efficacy analysis in a single-arm interventional study. Objectives We developed a brain-computer interface-triggered functional electrical stimulation therapy (BCI-FEST) system for clinical application and conducted an interventional study to (1) assess its feasibility and (2) understand its potential clinical efficacy for the rehabilitation of reaching and grasping in individuals with sub-acute spinal cord injury (SCI). Setting Spinal cord injury rehabilitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…Detailed clinical results from the study with sub-acute participants have been reported elsewhere. 24 In general, most participants experienced improvements in upper limb motor function. Three out of five participants demonstrated clinically significant improvements on self-reported assessments of independence, used as primary outcome measures.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Detailed clinical results from the study with sub-acute participants have been reported elsewhere. 24 In general, most participants experienced improvements in upper limb motor function. Three out of five participants demonstrated clinically significant improvements on self-reported assessments of independence, used as primary outcome measures.…”
Section: Discussionmentioning
confidence: 96%
“…We conducted two interventional studies to assess the feasibility and efficacy of BCI-FEST for upper limb rehabilitation for individuals with sub-acute (less than six months after injury) 24 and chronic (at least 24 months after injury) SCI. Participants of both studies were adults with traumatic incomplete SCI at the C4-C7 level and AIS B-D.…”
Section: Methodsmentioning
confidence: 99%
“…The EEG data used for the stimulation interference analysis in this report were acquired from eight participants in two studies investigating the feasibility of delivering BCI‐FEST intervention in individuals with cervical SCI. One study included five individuals with subacute SCI 27 . The other study is ongoing, and thus far, data have been collected from three individuals with chronic SCI.…”
Section: Methodsmentioning
confidence: 99%
“…All of them had an incomplete traumatic SCI at the C4 or C5 level (B‐D AIS) 28 . The clinical scores in the subacute population 27 and the BCI performance figures from all eight participants have been reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…This study was a sub-study conducted within two single arm interventional studies that aimed at assessing the feasibility and efficacy of EEG-Triggered Functional Electrical Stimulation Therapy for Upper Limb Rehabilitation. 22 Inclusion criteria for study 1 were: (a) traumatic SCI classified as American Spinal Injury Association Impairment Scale (AIS) B-D, (b) SCI less than six months prior to baseline assessment, (c) neurological level of injury between C4 to C7 and (d) expected length of stay of at least 80 days at the time of study initiation. The exclusion criteria were (a) history of seizure disorder not effectively managed by seizure medications, (b) an existing electrical stimulation device (e.g.…”
Section: Methodsmentioning
confidence: 99%